Development of a fermented quinoa beverage with autochthonous lactic acid bacteria - Fontana, Luisina; Peralta, Guillermo H.; Bergamini, Carina; Beret, María Victoria; Caballero, Soledad; Ale, Analía; Nicola, Giuliano; Forzani, Liliana; Vinderola, Gabriel; Puntillo, Melisa (Frontiers in Microbiology, 2026)
IntroductionThe growing demand for plant-based functional foods has driven research into non-dairy fermented alternatives that can deliver live microorganisms and potential health benefits. The pseudocereal Quinoa is a substrate of interest for lactic acid fermentation. This study aimed to develop a fermented quinoa-based beverage using autochthonous lactic acid bacteria (LAB) strains with technological and functional potential.MethodsSix LAB strains previously isolated from plant sources were screened for growth kinetics in an animal-free medium and in quinoa extract (QE). Lactiplantibacillus plantarum LpAv and Limosilactobacillus fermentum Lf2, an exopolysaccharide (EPS)-producing strain, were selected for beverage development. Fermentation parameters, rheological and biochemical profiles, peptide release, and sensory attributes were evaluated. An animal trial assessed immunomodulatory and antioxidant capacity in BALB/c mice that received fermented QE.ResultsBoth strains were able to acidify QE to pH < 4.5 within 8 h, ensuring microbiological safety. EPS production by Lf2 improved viscosity and texture, while mixed fermentation enhanced lactic acid yield and impacted on peptidic profiles, indicating synergistic proteolytic activity. LAB remained viable (>8 log CFU/mL) after 28 days at 4 °C. Sensory testing (n = 111 participants) showed moderate acceptability, improved by artificial flavoring. In mice, fermented QE increased intestinal IL-10 and IFN-γ levels and elevated hepatic catalase and superoxide dismutase activities, suggesting antioxidant and immune-modulatory effects without bacterial translocation.ConclusionThis work demonstrates the feasibility of producing a safe, stable, and functionally active fermented quinoa beverage using locally sourced LAB. The combination of L. plantarum LpAv and L. fermentum Lf2 improved both technological and functional properties, supporting their potential as starter cultures for plant-based probiotic foods.